Impact of autumn (fall) dormancy rating on growth and development of seedling lucerne - Ta, H.T.; Teixeira, E.I.; Moot, D.J. (Journal of New Zealand Grasslands, 2016)
To quantify the influence of autumn (fall) dormancy (FD) on DM production and phenological development during the seedling phase, three lucerne genotypes with contrasting ratings were grown at Lincoln University, New Zealand. A dormant (FD2), a semi-dormant (FD5), and a winter-active (FD10) genotype were inoculated and sown at a rate of 290 plants/m2 on 8 October 2014. By the end of the seedling phase (15 January 2015) the FD10 genotype had produced 20% higher shoot yield and 17% higher root yield than the other two genotypes. The percentage of total biomass partitioned to roots (Proot) was 50% for all genotypes. Total plant biomass (root + shoot yields) was 6.55 t DM/ha for FD10 compared with 5.57 t DM/ha for FD 2 and FD5. Plant height at the open-flower stage was 39.5 cm for FD10 compared with 34.5 cm for FD5 and 33.5 cm for FD2. Maximum leaf area index was similar amongst genotypes at 2.5. However, individual leaf area was 142, 119 and 111 cm2/stem for FD10, FD5 and FD2, respectively. The phyllochron was 52oCd per primary leaf (base temperature of 1oC) and consistent amongst genotypes. The number of primary leaves and branches were also conservative at 17 and 14/shoot, respectively. Therefore, differences in shoot yield among these lucerne genotypes during the seedling stage were mainly due to differences in plant height and individual leaf area expansion per plant. This led to greater light interception and therefore higher total biomass accumulation for FD10 than for the other two genotypes. Keywords: alfalfa, autumn, Medicago sativa L., phyllochron